2020
DOI: 10.5114/aoms.2018.81136
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of thyroid nodules and thyroid cancer in thyroidectomized patients with Graves’ disease

Abstract: Introduction: Incidental thyroid cancers are frequently detected in patients operated on for Graves' disease (GD). There are no clear data about the incidence and risk factors of incidental thyroid cancer in operated GD patients. The aim of this study is to evaluate the risk of thyroid carcinoma in surgically treated GD patients. Material and methods: The data of 121 GD patients who underwent total thyroidectomy in a single center between 2005 and 2015 were retrospectively evaluated. The diagnosis of thyroid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…Unlike most previous studies investigating the prevalence of thyroid cancer in GD patients who underwent thyroidectomy, the present study enrolled all GD patients with thyroid cancer who were treated at three tertiary hospitals. Data from previous studies regarding the prevalence of coexisting thyroid cancer in GD patients assessed preoperatively by US are summarized in Supplemental Table S2 [9,16,[22][23][24][25][26][27][28][29][30]. Studies using US to find thyroid nodules reported varying rates of concomitant thyroid cancer in GD patients were reported (3.3% to 28.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike most previous studies investigating the prevalence of thyroid cancer in GD patients who underwent thyroidectomy, the present study enrolled all GD patients with thyroid cancer who were treated at three tertiary hospitals. Data from previous studies regarding the prevalence of coexisting thyroid cancer in GD patients assessed preoperatively by US are summarized in Supplemental Table S2 [9,16,[22][23][24][25][26][27][28][29][30]. Studies using US to find thyroid nodules reported varying rates of concomitant thyroid cancer in GD patients were reported (3.3% to 28.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of thyroid cancer in GD patients varies widely, but a recent meta-analysis found a roughly 2.5-fold higher rate of thyroid cancer in GD patients than in the general population [4]. Early findings suggested that GD has a protective effect against thyroid cancer [5][6][7], but recent studies have revealed a higher incidence of thyroid cancer in patients with GD, particularly surgically treated patients [8,9]. Two nationwide cohort studies in Taiwan and Sweden evaluated the association between thyroid cancer and GD, and both found a higher incidence of thyroid cancer during the early GD follow-up period [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Комісаренка НАМН України» за період із 2008 по 2019 рік (1854 випадки), а потім серед них -усі пацієнти з остаточним патологічним діагнозом -«рак щитоподібної залози» (195 випадків Проте частина ПТК визначається в пацієнтів із ХГ, яких було прооперовано за клінічними показниками без жодних ознак вузлових уражень під час УЗД на передопераційному етапі, та мають назву ВПТК. Вони переважно являють собою мікропухлини розміром до 10 мм, і їхнє клінічне значення є предметом обговорення протягом багатьох років [3,4,[9][10][11].…”
Section: матеріал і методиunclassified
“…It reduced the incidence of laboratory hypocalcaemia [18].However, only 32.61% of 92 participants had multinodular goitre. The rest of the patients were ill with cancer or toxic goitreconditions where hypocalcaemia occurs more often after surgery [19].…”
Section: Introductionmentioning
confidence: 99%